2018
DOI: 10.1038/s41467-018-06543-0
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant activation of non-coding RNA targets of transcriptional elongation complexes contributes to TDP-43 toxicity

Abstract: TDP-43 is the major disease protein associated with amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration with ubiquitinated inclusions (FTLD-TDP). Here we identify the transcriptional elongation factor Ell—a shared component of little elongation complex (LEC) and super elongation complex (SEC)—as a strong modifier of TDP-43-mediated neurodegeneration. Our data indicate select targets of LEC and SEC become upregulated in the fly ALS/FTLD-TDP model. Among them, U12 snRNA and a stress-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 70 publications
0
46
0
Order By: Relevance
“…Mechanistically, hsrω interacts with dFUS, and depletion of hsrω results in dFUS translocation into the cytoplasm and abrogation of its nuclear function [79]. Levels of hsrω are positively regulated by TDP-43 via direct binding of TDP-43 to the hsrω locus in Drosophila [29]. The human orthologue of Drosophila hsrω, stress-induced Satellite III repeat RNA (Sat III), has also been shown to be elevated upon TDP-43 overexpression in the frontal cortex of FTLD-TDP patients [29].…”
Section: Other Lncrnas Implicated In Alsmentioning
confidence: 99%
“…Mechanistically, hsrω interacts with dFUS, and depletion of hsrω results in dFUS translocation into the cytoplasm and abrogation of its nuclear function [79]. Levels of hsrω are positively regulated by TDP-43 via direct binding of TDP-43 to the hsrω locus in Drosophila [29]. The human orthologue of Drosophila hsrω, stress-induced Satellite III repeat RNA (Sat III), has also been shown to be elevated upon TDP-43 overexpression in the frontal cortex of FTLD-TDP patients [29].…”
Section: Other Lncrnas Implicated In Alsmentioning
confidence: 99%
“…Together, it seems very likely that a functional equivalent of Drosophila orthologue is present in diverse dipterans as well, specific identification of which would need multi-pronged comprehensive cytogenetic, cell biological and genomic approaches. Functional similarity between the cell stress-inducible Sat III repetitive transcripts in human cells and the hsrω transcripts (Chung, et al, 2018;Jolly and Lakhotia, 2006) suggests that gene loci producing lncRNAs functionally analogous to hsrω transcripts indeed exist in diverse taxa as well.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the tandem repeats of the hsrω gene discharge their common functions despite the sequence variations. Interestingly, the Human repetitive Sat III sequences, functional equivalents of the hsrω gene (Chung, et al, 2018;Jolly and Lakhotia, 2006), do not show any similarity with tandem repeats of the hsrω gene but still perform comparable functions. As known for many lncRNAs, especially for those associated with membraneless phase-separated nuclear sub-structures, the secondary and higher order structures attained by the specific lncRNA orthologue are critical Lin, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Using tissues from postmortem ALS/ FTLD patients, TDP43 was associated with upregulation of the snRNA U12 and the ncRNA Hsrw (stressinduced satellite III repeat RNA), both of which are linked to neurodegeneration in ALS/FTLD. Mechanistically, upregulation of U12 snRNA and Hsrw is caused by an interaction between TDP43 and transcription elongation factor ELL2, a shared component of the little elongation complex and super elongation complex [131]. Using iCLIP in FTLS-TDP/ALS postmortem tissues, it was also shown that NEAT1 interacts with TDP43 and FUS/TLS [132,133].…”
Section: Ncrnas In Other Mechanisms Of Ad Pathogenesismentioning
confidence: 99%